Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s40985-018-0107-6
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding and rotavirus vaccination are associated with decreased diarrheal morbidity among under-five children in Bahir Dar, northwest Ethiopia

Abstract: BackgroundMore than one in every ten (14%) of under-five child deaths is associated with diarrheal morbidity in Ethiopia. Although Ethiopia has implemented different health interventions like its immunization program, childhood diarrhea morbidity, on which literature is limited, continues as a public health problem. Hence, the aim of this study was to assess the prevalence of diarrheal morbidity and associated factors among under-five children in Bahir Dar, northwest Ethiopia.MethodA community based cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 19 publications
4
18
0
Order By: Relevance
“…is study result agreed with the previous study report from India [30]. It is also associated with infectious disease and diarrheal morbidity [31]. is might be preventive effect of the vaccine especially infectious disease and diarrhea which leads to malnutrition.…”
Section: Discussionsupporting
confidence: 91%
“…is study result agreed with the previous study report from India [30]. It is also associated with infectious disease and diarrheal morbidity [31]. is might be preventive effect of the vaccine especially infectious disease and diarrhea which leads to malnutrition.…”
Section: Discussionsupporting
confidence: 91%
“…The result of our study finding indicated that children who were not received the rotavirus vaccine were 2.5 times more likely to develop diarrheal diseases as compared to those children who were received the rotavirus vaccine. This finding was in line with the studies conducted at Harena Buluk Woreda, Bahir Dar, and Debre Berhan in Ethiopia (31,28,32) and in sub-Saharan Africa, Cameroon, and Madagascar (33,34). These findings were reported that the rotavirus vaccine showed a significant association with the occurrence of diarrheal diseases among under-five children.…”
Section: Hand Washingsupporting
confidence: 89%
“…From these 17 articles were excluded due to the inclusion criteria. Among excluded studies, three of the studies were excluded because they didn't report our outcome of interests [73,74,75]. Two studies conducted among HIV infected mothers [76,77].…”
Section: Resultsmentioning
confidence: 99%